The Implementation of Charles Taylor’s Recognition Theory in Multicultural Education: Constructing a Model for Identity Empowerment in the School Context - Setia Paulina Sinulingga; Rr. Siti Murtiningsih; Hastanti Widy Nugroho (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to analyze the implementation of Charles Taylor’s theory of recognition within the context of multicultural education at Bina Kasih Christian High School in Jambi, Indonesia. Methodology: This research uses a qualitative approach with a case study method. Data were collected using in-depth interviews, participatory observation, and document analysis. Thematic analysis was conducted using NVivo 12 software. Tools include audio recorders, field notes, and school policy documents. Main Findings: The school implements recognition-based strategies such as interfaith dialogue, inclusive curriculum design, and community engagement. However, discrepancies remain between policy and practice, with stereotypes still influencing student interactions. The school’s religious identity influences how recognition is applied, requiring careful balancing of institutional and student values. Novelty/Originality of this study: This study introduces a new application of Taylor’s theory of recognition in an Indonesian educational setting, which is rarely explored. It advances current knowledge by linking philosophical recognition theory with practical multicultural education, offering insights for inclusive policy and curriculum development.